Formation of Strategy and Organizational Learning in a Complex Organization: A Case Study at the Military Fire Brigade of Espírito Santo in Brazil - Júnior, Roberto Rodrigues Souza; Cerqueira, Alexandre Santos; Gasparini, Adriana Schinaider Rigoni; Dumer, Miguel Carlos Ramos; Mendonça, Mark Miranda; Oliveira, Lorrara Silvya Imagawa (Archives of Business Research, 2023)
This study aims to investigate how the implications of learning, in an environment of high unpredictability, impact on the formation of the strategy of the Military Fire Brigade of Espírito Santo. For this, it analyzed the transition of the Strategic Planning (SP) cycle from 2011-2014 to 2015-2019, delimiting this analysis in senior management. As a theoretical foundation, the concepts of strategy formation, emerging strategies and elements of complexity are addressed, especially the role of learning in strategic management. This is a qualitative study, which adopted the single case study method. In data collection, document analysis and semi-structured interviews were carried out. In the data analysis, through the technique of qualitative data analysis, categories of results were established. Through the results, it was evidenced that strategies not carried out in a SP, were formed as emerging strategies in another, including preponderant characteristics of the elements of complexity; it was found that the 2015-2019 strategic planning was formulated with less prescriptive objectives than the previous one, which allowed for greater flexibility in implementation. Finally, in the relationship: learning, dynamism of environmental changes and strategy formation, the cyclical nature of this process was verified.